The Phenomenon of “Marriage Is Scary” and the Marriage Readiness of Generation Z: A Study of Family Law Students from an Islamic Law Perspective - Siska Andriani; Misran Misran; Gamal Akhyar (MAQASIDI: Jurnal Syariah dan Hukum, 2026)
The phenomenon of Marriage is Scary that develops on social media is one of the discourses that affects the way the younger generation views the institution of marriage. This narrative often features various domestic conflicts such as divorce, domestic violence, infidelity, and economic pressures which then form the perception that marriage is an institution full of risks. This condition has the potential to affect the readiness to marry of the younger generation, especially Generation Z who grew up in a digital environment and are very exposed to information through social media. This study aims to analyze the perception of Family Law students towards the phenomenon of Marriage is Scary, its influence on the marriage readiness of Generation Z, and review it from the perspective of Islamic law. This research uses a qualitative approach with phenomenological methods. The research data was obtained through in-depth interviews, observations, and documentation of students of the Department of Family Law UIN Ar-Raniry who actively use social media. Data analysis was carried out in a descriptive-analytical manner by interpreting the experience and meaning of the informants to the phenomenon being studied. The results of the study show that  the phenomenon of Marriage is Scary is found in various forms of social media content that display domestic conflicts, thus giving rise to the perception that marriage has various risks and challenges. This phenomenon affects the readiness to get married of Generation Z by encouraging a more cautious, selective attitude, and postponing marriage until they have more mature mental, emotional, and economic readiness. From the perspective of Islamic law, marriage is seen as mitsaqan ghalizhan which aims to form a family that is sakinah, mawaddah, and warahmah. The phenomenon of Marriage is Scary should not be interpreted as a reason to reject marriage, but as a social reflection that encourages the younger generation to prepare themselves more thoroughly before entering domestic life.